Use of mineral nutrients and surface-active substances in a biodegradation process modulation - Cejková, A; Masák, J; Jirků, V (Folia microbiologica, 1997)
The capability of a bacterial population to degrade oil hydrocarbons and naphthalene was found to be markedly enhanced by an optimized P:N ratio as well as by proper application of a surface-active compound. The importance of this optimization procedure was shown by both laboratory and technologically performed experiments.
Keywords: Chromatography, High Pressure Liquid; minerální olej; Serratia; vysokoúčinná kapalinová chromatografie; povrchově aktivní látky; Naphthalenes; gramnegativní aerobní bakterie; biodegradace; Surface-Active Agents; naftaleny; Octoxynol; Fuel Oils; Biodegradation, Environmental; biomasa; aromatické uhlovodíky; Chromatography, Gas; oktoxynol; Gram-Negative Aerobic Bacteria; topné oleje; Biomass; Mineral Oil; chromatografie plynová; Hydrocarbons, Aromatic